Molecular analysis of Kefiran exopolysaccharide: Interactions with vitamins, amino acids, monosaccharides, lipids, and Toll-like receptor 4 - ANDRADE, Laudelina Ferreira de; COSTA, Rebeca Santana da; FILA, Melissa Biazzi; SANTOS, Daniela Cácia dos; SOUZA, Tamirys Caroline Silva; AGUILAR, Charles Martins; SANTOS, Sérgio Henrique Sousa; BRANDI, Igor Viana; LESCANO, Caroline Honaiser; OLIVEIRA, Ivan Pires de (Food Science and Technology, 2024)
Kefir grains are composed of a consortium of microorganisms, which are enveloped in a matrix of exopolysaccharides called kefiran, with an almost equal proportion of D-glucose and D-galactose, produced by lactic acid bacteria of the genus Lactobacillus. Associated with a diversity of proteins and lipids, kefiran supports the symbiotic cellular structure and protects it against external influences, such as nutrient deficiencies, dehydration, bacteriophages, toxicity, and osmosis. Kefiran has attracted the attention of the scientific community due to its functional properties, and its role in modulating the immune system is the most studied and has potential for exploration. However, the biopolymer has a complex molecular structure and its physical and chemical properties still require investigation. The present study addresses the interaction between the kefiran tetramer and various compounds: trivalerate triacylglycerol; monosaccharide — D-glucose; fat-soluble vitamins such as vitamin A — retinol and vitamin D — cholecalciferol; water-soluble vitamins such as vitamin B2 — riboflavin and vitamin C — ascorbic acid; and amino acids such as positive side chain histidine, negative aspartate, polar asparagine, and hydrophobic isoleucine. From its molecular properties and experimental results from the literature, we discuss the role of kefiran in acting similarly to the carbohydrate portion of lipopolysaccharides in the Toll-like receptor and myeloid differentiation factor 2 system, activating the immune system.